Environmental Awareness and Environmental Management Practices: Mediating Effect of Environmental Data Distribution - SAEHU, Muhammad Syaiful; DIAH, Ahyar Muhammad; JULCA-GUERRERO, Felix; HUERTA-SOTO, Rosario; VALDERRAMA-PLASENCIA, Lorenzo (Journal of Environmental Management and Tourism, 2022)
This study investigates how environmental awareness of suppliers affects the distribution of products and services and management performance of environmental data using three key indicators: MPI (Management Performance Indicator), OPI (Operational Indicator Index), ECI (Environmental Condition Indicator). In order to prove these relations, the research models and hypotheses were established. After collecting 295 samples of effective responses from suppliers, an experimental analysis was conducted using structural equation modeling. The main findings reveals that the environmental awareness of suppliers influence the distribution and the representation of environmental data to the management with mediating effect on the relationship between suppliers and environment. This study has important significances: an academic one, that the scope of environmental awareness was extended from the consumer to the organizational perspective, especially to suppliers; another practical due that it has increased environmental awareness of suppliers improving the environmental management performance; and also, an educational with positive implications for the dissemination of environmental information.